(untitled) (Journal of Dhaka Medical College, 2015)
Background: Hydatid disease is a zoonotic disease caused by Echinococcus granulosus. In humans, lungs are the second common organ involved after liver. Surgical treatment is considered gold standard. Different surgical techniques has developed. However, head to head comparison of these has not yet been done in our country. Methods: A prospective randomized study was done in the Department of Thoracic Surgery, National Institute of Diseases of the Chest and Hospital between July 2004 and June 2006. Patients with pulmonary hydatid disease were offered two surgical techniques, enucleation with or without capitonnage. Group I was offered enucleation of cyst with closure of bronchial opening. Group II was offered enucleation of cyst with capitonnage. Results: 43 patients (age range 7 45 years, mean 25 years) having hydatid disease of the lung were enrolled in the study. Group I involved 23 patients, Group II involved 20 patients. There were 15 males and 28 females. Presenting complaints were chest pain [76.7%], cough without sputum [46.5%], haemoptysis [30.2%], respiratory distress [27.9%], cough with sputum [11.6%] while 23.2% were asymptomatic. The right lung was affected more [65.11%] than left lung [23.3%] and bilateral disease was found in 11%. Postoperatively, in group I, 12.9% developed air-leakage, 4.3% wound infection. In group II, 20% developed air-leakage, 5% haemorrhage and 5% empyema. None of the patient in the former group had to stay in the hospital for >15 days, where as 10% of the latter group had to stay in hospital for >15 days. The hospital stay was found to be significantly higher in the latter group compared to the former group (p < 0.05). There was no significant difference between groups in the development of haemorrhage, empyema, wound infection and broncho-pleural fistula. There was also no significant difference in the rate of recurrence. No anaphylaxis or death occurred in either group. Conclusion: Capitonnage offered no added benefit rather increasing complications. So enucleation followed by closure of bronchial opening may be a reasonable approach. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22702 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 94-101